2017
DOI: 10.15255/cabeq.2017.1092
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Lipid Production of Dunaliella tertiolecta by Manipulating the Interactive Effect of Salinity and Nitrogen

Abstract: Low lipid yield is a major bottleneck towards the scale-up application of microalgae for biodiesel production. The focus of this study was to improve the lipid production of Dunaliella tertiolecta (a marine microalga) by altering the concentration of salinity and nitrogen (as nutrients). The unique aspect of this study was to investigate the interactive effect of nitrogen and salinity on lipid production and their correlation with biomass yield and nitrogen uptake. In this experiment, microalgae were grown und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Marine microalgae can utilise inorganic nitrogen for their growth and metabolic activities and increase their biomass concentrations in conjunction with the nitrogen-enriched condition (Rizwan et al, 2017). The present study findings also revealed that the increment of nitrogen (NaNO 3 ) supply in the medium significantly increased biomass production of T. chuii, but the contrary result was found for decreased concentrations of nitrogen.…”
Section: Resultssupporting
confidence: 58%
“…Marine microalgae can utilise inorganic nitrogen for their growth and metabolic activities and increase their biomass concentrations in conjunction with the nitrogen-enriched condition (Rizwan et al, 2017). The present study findings also revealed that the increment of nitrogen (NaNO 3 ) supply in the medium significantly increased biomass production of T. chuii, but the contrary result was found for decreased concentrations of nitrogen.…”
Section: Resultssupporting
confidence: 58%
“…Jahnke and White (2003) demonstrated that while different Dunaliella species can grow in a wide range of salinities (2.9 -175 PSU) only D. tertiolecta can grow in salinity lower than 3 PSU, as we also observed here. A decrease in D. tertiolecta growth under hyposalinity was previously observed (Jahnke and White 2003;Rizwan et al 2017). In addition, hyposalinity was found to lead to an increase in D. tertiolecta cell size, which had reduced F v /F m levels and a smaller ascorbate pool along with an increased pool of α-tocopherol and total glutathione (Jahnke and White 2003).…”
Section: Cell Growth In Response To Salinity Decreasesupporting
confidence: 59%
“…7 A similar pattern of lipid accumulation at intermediate salinity was also described in the halotolerant Dunaliella tertiolecta. 92 Interestingly, in the halophile Dunaliella salina, cell lipid content increased with salinity up to 2 M NaCl. 50 The fluctuating response of total lipid between close strains may be partly influenced by the existence of high intraspecific variability 93 and eventual evolutionary adaptations to specific salinity niches.…”
Section: Theinter Ac Tingeffec Tof Salinit Yandculturecond Iti On Son Lipidcontentinmi Croalg Aementioning
confidence: 98%